Activation of farnesoid X receptor downregulates visfatin and attenuates diabetic nephropathy. (5th January 2016) - Zhou, Baoshang; Feng, Bing; Qin, Zhexue; Zhao, Youguang; Chen, Yu; Shi, Zhengmin; Gong, Yi; Zhang, Jing; Yuan, Fahuan; Mu, Jiao
Abstract: Visfatin, a recently discovered adipocytokine, has been shown to have an important role in the pathogenesis of diabetic nephropathy (DN). The farnesoid X receptor (FXR), a ligand-activated nuclear receptor, plays a protective role in DN. The regulation between FXR and visfatin and their interaction in DN has not been well established. In this study, we reported that FXR agonist GW4064 reduced high glucose induced human mesangial cells (HMCs) inflammation, fibrosis and proliferation by downregulating visfatin expression, which can be blunted by exogenous visfatin treatment. Moreover, luciferase reporter assay showed FXR regulated visfatin transcription activity probably by binding to the −1607 bp and −1192 bp region of the visfatin promoter. In vivo study also showed that GW4064 ameliorated the progression of DN in db/db mice with a decreased visfatin expression. These findings suggest that FXR activation delayed the progression of diabetic nephropathy and this effect is through downregulating visfatin. Highlights: FXR activation downregulates visfatin expression in high glucose induced HMCs. FXR activation suppresses inflammatory responses and proliferation via inhibiting visfatin in high glucose induced HMCs. FXR activation suppresses TGF-β/Smad and ECM expression via inhibiting visfatin in high glucose induced HMCs. FXR activation suppresses visfatin transcription activity. FXR agonist reduces visfatin expression and ameliorates diabetic nephropathy in vivo.